A Miniaturized Broadband and High Gain Planar Vivaldi Antenna for Future Wireless Communication Applications - Permanand Soothar; Hao Wang; Chunyan Xu; Yu Quan; Zaheer Ahmed Dayo; Muhammad Aamir; Badar Muneer (International Journal of Antennas and Propagation)
This paper presents a new miniaturized planar Vivaldi antenna (PVA) design. The proposed antenna structure consists of an aperture tapered profile and cavity stub fed with a simple 50 Ω strip line feeding network. The designed PVA offers versatile advantages, including the miniaturized size and simple design, and exhibited an outstanding performance compared to the latest reported literature. The antenna occupies a minimal space with an electrical size of 0.92λ0 × 0.64λ0 × 0.03λ0. The antenna achieves an excellent relative impedance bandwidth 117.25% at 10 dB return loss, peak realized gain of 10.9 dBi, and an excellent radiation efficiency of 95% at the specific resonances. The antenna’s optimal features, that is, broadband, high gain, and radiation efficiency, are achieved with efficient grooves based approach. Besides, the proposed antenna results are also analyzed in the time domain, which shows the excellent group delay performance <2 ns in the operational band. The proposed antenna exhibited a stable far-ﬁeld radiation pattern in orthogonal planes and strong distribution of current at multiple resonances. Simulation and the measured result show a good agreement. The proposed antenna has achieved optimal performance and is suitable for future wireless communication applications.